Strategi Konseptual Dalam Manajemen Aktivitas Personalia Pada Perusahaan Agen Pelayaran Peti Kemas - Mawardi, Kholid; Negara, Gembong Satria; Guritno, Suryo; Yulianto, Yulianto; Santoso, Wahyudi; Emha, Faresh (FEB Universitas Maritim Semarang, 2025)
The authors of the article have chosen a company acting as an agent for a container shipping line because the company seeks to decrease its service failures and reduce the chaotic nature of its activities by systematizing them from a scientific point of view and refining its operations at the managerial level. Employees of the company are responsible for activities such as a search for customers, price offers, contacting clients, the conclusion of contracts, coordination of cargo transportation, document control, invoicing and payment control. Proper execution of these operations ensures the quality of services provided by the container line agent. The learning organization concept, situational management theory and total quality management theory are applicable to the management of the personnel activity process in the line. In terms of management functions, planning is more suitable for activities such as searching for customers, price offers, conclusion of contracts and invoicing; organizing is more required when searching for customers, contacting them and concluding contracts; leading is more suitable for activities such as contact with clients, conclusion of contracts and payment control; control is more required when contacting customers, coordinating cargo transportation, invoicing and controlling payment. A conceptual approach that theoretically reveals the principles and possibilities of the company’s activities in the container shipping line can serve as the basis for future empirical research to identify problems in its personnel activity management.